2012
DOI: 10.2527/jas.2011-4973
|View full text |Cite
|
Sign up to set email alerts
|

Loading gantry versus traditional chute for the finisher pig: Effect on welfare at the time of loading and performance measures and transport losses at the harvest facility1

Abstract: The objectives of these studies were to evaluate the loading system effects [traditional chute (TC) vs. prototype loading gantry (PLG)] on i) welfare measures at loading and ii) performance measures and transport losses at the harvest facility for the market-weight pig (Sus scrofa). This study compared first pull (FP), which was the first group of pigs, and close out (CO), which was the last group of pigs marketed from a finishing facility. Experiment 1 evaluated 74 loads for welfare measures at loading on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Sin embargo, un pequeño porcentaje de animales mueren y otros presentan dificultad para caminar durante el desembarque, lo que se conoce comúnmente como «cerdos no ambulatorios» (Sutherland et al, 2009a;Johnson et al, 2013). La presencia de cerdos no ambulatorios o que mueren en cualquier etapa durante el proceso de comercialización se denominan «pérdidas por transporte» (Berry et al, 2012).…”
Section: Introductionunclassified
“…Sin embargo, un pequeño porcentaje de animales mueren y otros presentan dificultad para caminar durante el desembarque, lo que se conoce comúnmente como «cerdos no ambulatorios» (Sutherland et al, 2009a;Johnson et al, 2013). La presencia de cerdos no ambulatorios o que mueren en cualquier etapa durante el proceso de comercialización se denominan «pérdidas por transporte» (Berry et al, 2012).…”
Section: Introductionunclassified
“…Garcia et al (2019) found that a pig's heart will beat faster on a steep ramp. The maximum recommended angle for a cattle is 20 • 2008) and for pigs 15 • (Berry et al, 2012).…”
Section: Problems With the Physical Environment Such As Slipping And Falling On Floors And Rampsmentioning
confidence: 99%
“…These requirements included that 1) all facilities and handling equipment must be designed based on the behavioral and physiological attributes of the pigs, 2) design must provide a continuous unidirectional flow of pigs from the pen of origin to a target location, and 3) design must be compatible with site design, facility structure, and transport system. To facilitate these design requirements, key components include flooring profile and texture and slope of the loading chute (Berry et al, 2012).…”
Section: Facility Designmentioning
confidence: 99%